2000
DOI: 10.1046/j.1365-2036.2000.00868.x
|View full text |Cite
|
Sign up to set email alerts
|

Failure of a motilin receptor agonist (ABT‐229) to relieve the symptoms of functional dyspepsia in patients with and without delayed gastric emptying: a randomized double‐blind placebo‐controlled trial

Abstract: SUMMARYIntroduction: Motilin-receptor agonists are prokinetics; whether they relieve the symptoms of functional dyspepsia is unknown. We aimed to test the ef®cacy of the motilin agonist ABT-229 in functional dyspepsia patients with and without delayed gastric emptying. Methods: Patients were randomized with postprandial symptoms and documented functional dyspepsia by endoscopy (n 589 in intention-to-treat analysis). Patients were assigned to either the delayed or normal gastric emptying strata, based on a vali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
149
0
7

Year Published

2003
2003
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 207 publications
(157 citation statements)
references
References 31 publications
(38 reference statements)
1
149
0
7
Order By: Relevance
“…Unfortunately, however, identifying the abnormal pathophysiologic mechanisms that underlie the development of FD symptoms has not directly altered treatment strategies. For example, several studies have demonstrated a lack of relationship between FD symptoms and gastric emptying ( 149,185,186 ). Since tests to measure gastric accommodation are not readily available (barostat and single-photon emission computed tomography) or expensive, invasive and uncomfortable (barostat), and because delays in gastric emptying are not accurately related to symptoms, routine motility tests for patients with FD are not recommended.…”
Section: Conditional Recommendation Very Low Quality Evidencementioning
confidence: 99%
“…Unfortunately, however, identifying the abnormal pathophysiologic mechanisms that underlie the development of FD symptoms has not directly altered treatment strategies. For example, several studies have demonstrated a lack of relationship between FD symptoms and gastric emptying ( 149,185,186 ). Since tests to measure gastric accommodation are not readily available (barostat and single-photon emission computed tomography) or expensive, invasive and uncomfortable (barostat), and because delays in gastric emptying are not accurately related to symptoms, routine motility tests for patients with FD are not recommended.…”
Section: Conditional Recommendation Very Low Quality Evidencementioning
confidence: 99%
“…73 Motilin-receptor agonists can also act as prokinetics, but a recent study showed that the motilin agonist ABT-229 was of no value for relief of symptoms in functional dyspepsia, compared with placebo. 74 Moreover, erythromycin and related compounds have a disadvantage of reducing the meal-induced relaxation of the proximal stomach. 75 …”
Section: Prokinetic Agentsmentioning
confidence: 99%
“…As a result, more potent motorstimulating EM derivatives were developed without antibiotic activity: the motilides (Omura et al, 1987). Recently the clinical development of the most promising motilide ABT-229 was stopped because of its failure to improve symptoms in patients with functional dyspepsia with normal or delayed gastric emptying (Talley et al, 2000) and in patients with type 1 diabetes mellitus (Talley et al, 2001). The authors of the studies with ABT-229 concluded that there was no future for drugs with the prokinetic profile of the motilides, but others have argued that ABT-229 had undesirable properties that may be avoided in new motilides (Tack and Peeters, 2001;Camilleri, 2002).…”
mentioning
confidence: 99%